Multiband multiple‐input multiple‐output antenna with high isolation for future 5G smartphone applications. Issue 7 (11th April 2019) - Wang, Mingkai; Xu, Bin; Li, Yixin; Luo, Yong; Zou, Huanqing; Yang, Guangli
Abstract: A multiband high‐isolation multiple‐input multiple‐output (MIMO) antenna using balanced mode and coupled neutralization line (NL) is presented in this article. The balanced modes of dipole and loop antennas, which leads to good isolation intrinsically are used for the 8 × 8 MIMO in the LTE bands 42 (3400‐3600 MHz)/Chinese 5G band (3300‐3400 and 3400‐3600 MHz). The unbalanced mode of loop antennas, which optimized by decoupling structure are designed for the 4 × 4 MIMO in the LTE band 40 (2300‐2400 MHz). Therefore, the eight‐antenna array is formed by four dipole elements and four loop elements. The simulated and measured results show that the proposed antenna can cover 2300 to 2400 and 3300 to 3600 MHz, with reflection coefficient better than −6 dB and isolation higher than 15 dB. Good radiation performance and low envelope correlation coefficient can also be obtained. Specific absorption rate of user's hand is also discussed in this article.